Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00424-017-2076-x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts

Abstract: Metabolic disturbance and mitochondrial dysfunction are a hallmark of diabetic cardiomyopathy (DC). Resistance exercise (RE) not only enhances the condition of healthy individuals but could also improve the status of those with disease. However, the beneficial effects of RE in the prevention of DC and mitochondrial dysfunction are uncertain. Therefore, this study investigated whether RE attenuates DC by improving mitochondrial function using an in vivo rat model of diabetes. Fourteen Otsuka Long-Evans Tokushim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…In vivo, we also detected the expression of mitochondrial UCP2, which has been suggested to be positively associated with reduced cardiac efficiency in db/db hearts [35,36]. We found that the UCP2 level was higher than in non-diabetic hearts.…”
Section: Discussionsupporting
confidence: 51%
“…In vivo, we also detected the expression of mitochondrial UCP2, which has been suggested to be positively associated with reduced cardiac efficiency in db/db hearts [35,36]. We found that the UCP2 level was higher than in non-diabetic hearts.…”
Section: Discussionsupporting
confidence: 51%
“…The precise mechanism by which hyperglycemia impairs cardiac contraction is still unknown. However, increases in free fatty acid oxidation, oxidative stress, and mitochondrial dysfunction, as well as impaired glucose utilization in cardiac myocytes, seem to be associated with poor systolic and diastolic contractile capacity, even in patients without atherosclerotic coronary artery disease [2425]. In addition, impaired microvascular endothelial function, increased myocardial fibrosis, activation of the renin-angiotensin system, and sympathetic overactivity also contribute to HF [24].…”
Section: Cardiovascular Events In Patients With T2dmmentioning
confidence: 99%
“…Ca 2+ is a key metabolic enzyme activator in mitochondria, and mitochondrial Ca 2+ circulatory balance can be easily affected by intracellular Ca 2+ homeostasis (41, 42). Resistance exercise improves cardiac function and mitochondrial efficiency in hearts, of diabetic rat, which were accompanied by higher expressions of mitochondrial biogenesis proteins such as PGC-1α and mitochondrial transcription factor A (TFAM) (45). In addition, studies have shown that high intensity exercise can increase myocardial mitochondrial contents, but no change in moderate intensity exercise (46, 47).…”
Section: Pre-clinical Experiments About Physical Exercise and Dcmmentioning
confidence: 99%